Big fish are the best: Seed dispersal of Bactris glaucescens by the pacu fish (Piaractus mesopotamicus) in the Pantanal, Brazil - Galetti, Mauro [UNESP]; Donatti, Camila I.; Pizo, Marco Aurelio; Giacomini, Henrique C. [UNESP] (Wiley-Blackwell, 2008)
We studied the potential role as seed disperser of the pacu fish (Piaracrus mesopotamicus, Characidae) in the Pantanal of Brazil. The most important food item in the diet of the pacu in the wet season was fruits of the palm Bactris glaucescens found in the guts of 73 percent of all fishes collected (N = 70). We found a positive relationship between fish length, weight, and gape size and the number of intact seeds in their gut. Therefore, large pacus are especially important in dispersing B. glaucescens seeds within the studied system. Since the best seed dispersers are the largest fishes, which are preferred by commercial fisheries, we predict that the ongoing over fishing in freshwater ecosystems will have major impacts on the dispersal system of fish-dependent plants. We suggest that it is paramount to change the attitudes in fisheries management of fruit-eating fishes and urgent to evaluate the impact of fishing on forest regeneration.
Keywords: Arecaceae; ichthyochory; mutualism disruption; seed predation